Balancing the right to a private life and freedom of expression: is pre-publication notification the way forward?. Issue 1 (2nd January 2017) - Taylor, Louisa
ABSTRACT: This article considers whether newspapers should be under a requirement to notify subjects of stories which contain private information. The events of Mosley v UK provide the basis of discussion. The arguments for and against a pre-notification requirement are critically examined and the practical considerations of implementing the requirement are analysed. A few solutions to the problem of protecting privacy when newspapers want to publish private information are then discussed. It is considered that pre-publication notification is necessary to ensure that the privacy rights of subjects of stories are protected. Pre-publication notification will allow individuals to apply for interim injunctions and ensure that the story remains private. However, given the practical problems involved in implementing such a requirement, it is concluded that a pre-publication notification requirement will not be introduced for the foreseeable future.